L’efficacité économique du mode d’allocation des ressources naturelles - Hung, Nguyen (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
AbstractIn this paper, the decentralized economic allocation of a common property resource is fully characterized in a dynamic framework. Because of the externalities involved, this mode of allocation is shown to be inefficient. The extent and the causes of this inefficiency are discussed, with special emphasis on a kind of externality herein called the "appropriability". Finally, economic policies involving taxation, subsidy and user charge which purpose to bring about the social optimum are pointed out.